The Study of Plasma Activated Water Treatment for Microorganism in Soil - Millin, Arthur Marren; Mohd Razi, Rusyaidi Jazmiey; Ahmad Faiz Mat Zian @ Mat Zin; Roslan, Muhammad Sufi (Multidisciplinary Applied Research and Innovation, 2023)
In order to grow and develop, plants need food, just like all other livingthings. Plants require sixteen essential elements. Carbon, hydrogen, and oxygen areall found in the atmosphere and in soil water. The remaining 13 elements which arenitrogen, phosphorus, potassium, calcium, magnesium, sulfur, iron, zinc, manganese,copper, boron, molybdenum, and chlorine are either supplied by soil minerals and soilorganic matter or by organic or inorganic fertilizers. Thus, to increase the quality andgrowth rate of crops, farmers will use fertilizers. However, the usage of excessfertilizers lead to soil pollution and water pollution due to leaching of chemicals. Withthe usage of Plasma Activated Water (PAW), nutrients can be supplied to crops moreorganically and produce much less harm. PAW is also a good medium to stimulatethe growth of nitrogen fixation bacteria, nitrobacter, which is important in supplyingcontinuous dissolved nitrogen to plants. PAW contain various gaseous reactivespecies like OH, H2O2, NO and HNO as the result of plasma contact with the watersurface. This study is being carried out by treating different distilled water sampleswith different times of plasma treatment to find the optimal time of treatment. Thetreated water is then poured to microorganisms in soil to check whether it canstimulate the growth of microorganisms that boost plant growth. The significance ofthis study is to increase the nutrient quality of the soils without using any chemicalssuch as fertilizer as well to improve the nitrogen fixation process for plants. Tosummarize, the plasma treated water contains a high amount of N=O bond which alsoshows the presence of nitrite ion and the plasma treated water also enhances thegrowth of microorganism in soil. Therefore, this study is successful since the relationwith objectives is met